2023
DOI: 10.3390/ijms24108915
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Clinical Profile of Retinopathies Due to Disease-Causing Variants in Leber Congenital Amaurosis (LCA)-Associated Genes in a Large German Cohort

Ditta Zobor,
Britta Brühwiler,
Eberhart Zrenner
et al.

Abstract: To report the spectrum of Leber congenital amaurosis (LCA) associated genes in a large German cohort and to delineate their associated phenotype. Local databases were screened for patients with a clinical diagnosis of LCA and for patients with disease-causing variants in known LCA-associated genes independent of their clinical diagnosis. Patients with a mere clinical diagnosis were invited for genetic testing. Genomic DNA was either analyzed in a diagnostic-genetic or research setup using various capture panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 59 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…CEP290 was the most prevalent gene in our cohort (26%), followed by RPE65, CRB1, and GUCY2D, which each had a prevalence of 13%. In comparison, a recent study on a German cohort of 105 patients found their top causative genes to be CEP290 (21%), RPE65 (14%), CRB1 (11%), and RDH12 (8%) [31]. A Brazilian cohort of 152 patients with LCA/EOSRD reported that the top causative genes were CEP290 (21%), RPE65 (16%), CRB1 (14%), and RPGRIP1 (10%) [32].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…CEP290 was the most prevalent gene in our cohort (26%), followed by RPE65, CRB1, and GUCY2D, which each had a prevalence of 13%. In comparison, a recent study on a German cohort of 105 patients found their top causative genes to be CEP290 (21%), RPE65 (14%), CRB1 (11%), and RDH12 (8%) [31]. A Brazilian cohort of 152 patients with LCA/EOSRD reported that the top causative genes were CEP290 (21%), RPE65 (16%), CRB1 (14%), and RPGRIP1 (10%) [32].…”
Section: Discussionmentioning
confidence: 93%
“…The various global studies and their LCA-associated gene variant prevalence are presented in Figure 5. The studies included the Midwest US (our cohort), Germany [31], Brazil [32], China [33], Japan [28], and Australia [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triple knockout mice abca4(-/-)rdh8(-/-)rdh12(-/-) raised under cyclic light develop retinal degeneration at the age of 6 weeks, whereas at least 3 months are needed to demonstrate a similar level of retinal degeneration for double knockout mice abca4(-/-)rdh8(-/-) [ 113 ]. Mutations of RDH12 can cause early onset severe cone-rod dystrophy, Leber congenital amaurosis, retinitis pigmentosa, and pseudocoloboma-like maculopathy [ 114 , 115 , 116 , 117 , 118 ].…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 , 12 RP is a clinically and genetically heterogeneous disease where children or aged patients experience night blindness that progresses to complete loss of vision, 13 while LCA causes visual impairment in newborns. 14 , 15 There are over 200 different mutations along the CRB1 gene described to be causing early-onset RP in children or LCA without a clear genotype-phenotype correlation. 16 , 17 , 18 , 19 , 20 , 21 No treatment possibilities are available for patients with a mutation in the CRB1 gene.…”
Section: Introductionmentioning
confidence: 99%